Representation of Women in Javanese Patriarchal Culture in the Performance of Teater - M. Ridwan Hakim (Universitas Bunda Mulia, 2020)
This research attempts to analyze the representation of women in the Javanese patriarchy in a theater performance entitled 'Archeology of Beha' by Benny Yohannes, performed by the Ukm Teater Gabung Unsika. This research uses the theory of semiotic analysis (study of signs) by Roland Barthes. Barthes argues that the sign system is divided into denotations, connotations and myths. This research uses a qualitative approach that is descriptive and uses text research techniques. Thus, this study only describes the situation, makes descriptive, and illustrative, systematically. Based on the discussion, the results of the study show that the representation of women in the Javanese patriarchy in theater performances entitled 'Archeology of Beha' by Benny Yohannes performed by the UKM Theater Gabung Unsika, includes: Women experiencing sexual objectification; Women in the feminine role get weak views; Women experience injustices related to the dichotomy of domestic and public work; Women in the role of mothers have a very noble view; Women as Wives Experiencing Difficult Positions. Keywords: Women; Patriarchy; Semiotics; Theater.